2023
DOI: 10.3390/genes14101877
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Identification and Comparative Analysis of the Heavy-Metal-Associated Gene Family in Cucurbitaceae Species and Their Role in Cucurbita pepo under Arsenic Stress

Gerardo Flores-Iga,
Carlos Lopez-Ortiz,
Celeste Gracia-Rodriguez
et al.

Abstract: The heavy-metal-associated (HMA) proteins are a class of PB1-type ATPases related to the intracellular transport and detoxification of metals. However, due to a lack of information regarding the HMA gene family in the Cucurbitaceae family, a comprehensive genome-wide analysis of the HMA family was performed in ten Cucurbitaceae species: Citrullus amarus, Citrullus colocynthis, Citrullus lanatus, Citrullus mucosospermus, Cucumis melo, Cucumis sativus, Cucurbita maxima, Cucurbita moschata, Cucurbita pepo, and Le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…However, its specific function in the presence of As has not yet been fully elucidated [ 67 ]. The expression patterns of the Heavy Metal ATPase (HMA) family have been analyzed in Cucurbita pepo under As (V) stress [ 114 ]. The Cu/Ag clade members showed a positive modulation, especially CpHMA6, which exhibited high up-regulation in root and shoot tissues.…”
Section: Arsenic Extrusion Mechanismsmentioning
confidence: 99%
“…However, its specific function in the presence of As has not yet been fully elucidated [ 67 ]. The expression patterns of the Heavy Metal ATPase (HMA) family have been analyzed in Cucurbita pepo under As (V) stress [ 114 ]. The Cu/Ag clade members showed a positive modulation, especially CpHMA6, which exhibited high up-regulation in root and shoot tissues.…”
Section: Arsenic Extrusion Mechanismsmentioning
confidence: 99%
“…Among these cluster-accessory genes, several were frequently present, specifically two genes with no functional description available and a basic region leucine zipper (bZIP), potentially playing a similar role to the bZIP transcription factor ARR1/YAP8, which is both required for the transcription of ARR2 and ARR3 in S. cerevisiae (Wysocki et al, 2004) and activated by arsenite binding (Navarro et al, 2022). Additionally, two other cluster-accessory genes were found close to the cluster in several different Starship-related regions; TRX1, a thioredoxin both inhibited by arsenic and shown to confer resistance (Jovanovic et al, 2021;Lu et al, 2007;Park, 2020) and a heavy metal associated p-type ATPase, similar to pcaA, shown to confer resistance to cadmium and lead in Hephaestus, possibly involved in arsenic/arsenite transport (Antonucci et al, 2017;Flores-Iga et al, 2023;H. Yan et al, 2019).…”
Section: Expanding Upon the Arsenic Resistance Cluster Of Hephaestusmentioning
confidence: 99%